2015
DOI: 10.1590/1982-0224-20140082
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-based herbicide affects biochemical parameters in Rhamdia quelen (Quoy & Gaimard, 1824 and) Leporinus obtusidens (Valenciennes, 1837)

Abstract: Rhamdia quelen (silver catfish) and Leporinus obtusidens (piava) were exposed to a commercial formulation Roundup ® , a glyphosate-based herbicide at concentrations of 0.2 or 0.4 mg/L for 96 h. The effects of the herbicide were analyzed on the alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities and glucose in plasma, glucose and protein in the mucus layer, nucleotide hydrolysis in the brain, and protein carbonyl in the liver. The parameters were chosen, owing to a lack of information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…However, the results of previous studies showed that it was toxic to fish species (10,14). Loro et al (15) reported that glyphosate-based herbicide was toxic to Rhamdia quelen and Leporinus obtusidens. Sandun et al (16) reported that 96-hour LC 50 of glyphosate to Oreochromis niloticus was 16.7 mg.L -1 ; Da Cruz et al (17) also pointed out that glyphosate-based herbicide was toxic to fish as an aquatic organism.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of previous studies showed that it was toxic to fish species (10,14). Loro et al (15) reported that glyphosate-based herbicide was toxic to Rhamdia quelen and Leporinus obtusidens. Sandun et al (16) reported that 96-hour LC 50 of glyphosate to Oreochromis niloticus was 16.7 mg.L -1 ; Da Cruz et al (17) also pointed out that glyphosate-based herbicide was toxic to fish as an aquatic organism.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that the most evident toxic effect was the disturbance in several biochemical parameters followed by mortality and development malformations. These biochemical perturbations are accompanied by alterations in the metabolic and oxidative pathways (Loro et al 2015; Murussi et al 2016; Lopes et al 2017; Sobjak et al 2017; Persch et al 2018; Panetto et al 2019). In addition to these, genotoxic damage (Rodrigues et al 2019), hepatotoxicity (Santos et al 2017), histopathologic damage (Antunes et al 2017), immunotoxicity (Kreutz et al 2014), and alterations related to protein expression (Rocha et al 2015; Jaramillo et al 2017) were recorded in these studies with fish.…”
Section: Resultsmentioning
confidence: 99%
“…The glucose level was significantly reduced after acute exposure to this herbicide. Loro et al [57] also reported decreased plasmatic glucose levels and hypoglycemia after exposure to glyphosate-based herbicides. Hypoglycemia can be caused by stress, irritation, and rapid movements of the fish.…”
Section: Discussionmentioning
confidence: 97%